Music Creation of Taru Pule | Tabuh Kreasi Taru Pule - Antara, I Kadek Agus Dwi; Indra Sadguna, I Gde Made (GHURNITA: Jurnal Seni Karawitan, 2024)
Music creation Taru Pule was inspired by a personal experience that the artist saw. It felt the coolness and serenity of the beauty of the Pule tree, which is so big, solid, and towering with leaves waving in the wind, creating a relaxed and calm atmosphere. In Bali, the Pule tree is very sacred because it usually grows in holy places such as temples and cemeteries. Therefore, apart from depicting the coolness and serenity of the beauty of the Pule Tree, the stylist also wanted to give a sacred and majestic impression associated with processing the melody. Hence, the stylist used the Semar Pagulingan saih pitu gamelan as a medium of expression to create this atmosphere. The methods used in Taru Pule's work are three methods: the exploration method, namely the idea search stage; the improvisation method, namely the idea merging stage; and the forming method, namely the refinement stage. The musical work "Taru Pule" is composed of three parts, namely the first part, the second part, and the third part. The first part describes how the atmosphere is relaxed and calm under a tree; the second part depicts the silence and beauty when the wind blows the leaves. Apart from that, it also gives a sacred impression associated with processing the melody. The third part combines parts one and two with different melodies and a work duration of 10 minutes.